The impact of immigration on low-skilled natives - Johannsson, Hannes, author; Shulman, Steven, advisor; Bernasek, Alexandra, committee member; Jianakoplos, Nancy, committee member; Weiler, Stephan, committee member; Xing, Jun, committee member (Colorado State University. Libraries, 1999)
How do immigrants in the United States affect the labor market outcomes of less-skilled native workers? This dissertation addresses this question by analyzing first the effect low-skilled immigrants have on low-skilled natives in 70 metropolitan statistical areas, and then on 25 cities in which more than a quarter of the low-skilled population are immigrants. Specifically, I evaluate the impact immigrants with less than high-school education have on their native counterparts, as these individuals are most vulnerable to such labor supply shocks. Pooled cross-section data from 1994 to 1997 from the March supplements to the Current Population Surveys of the U.S. Census are the basis for the study. This research extends the current literature in several ways. First, using a fixed-effects model on pooled cross-sectional data provides increased efficiency of the estimators and thus more reliable results. Second, this study focuses on the short-run impact of immigration by looking at only a four year period, 1994-1997. This is important as it reduces the problem associated with factor mobility commonly observed in the migration literature. As immigrants arrive into an area, natives may simply drop out of the labor force and/or move out of the area. This potential departure out of the local labor force clearly may diminish the actual impact associated with immigration. Third, in addition to looking at the impact of immigration on annual income and unemployment, this study looks at labor force participation rates as well. This is a significant addition as it provides a potential explanation as to why previous studies have failed to find a consistent negative impact on income and employment. The results of this research indicate that immigrants have a statistically significant negative impact on the labor market outcomes of low-skilled native workers. More specifically, immigrants reduce the labor force participation rates of natives and as the immigrant intensity increases, the impact is compounded. The impact on annual income is also relatively large although not statistically significant. The results on unemployment rates are positive, suggesting that immigrants actually reduce the unemployment rates of natives, which is consistent with what one would expect given the large observed reduction in natives' labor force participation. This result is even more profound given the time period of the study. The fact that from 1994-1997 the United States experienced sustained economic growth suggests that low-skilled immigrants do indeed have an adverse impact on low-skilled natives.
Keywords: American studies; social structure